The role of Kurdish channels' cooking programs in the development of culinary arts among women) is a survey study( - Banaz Hama Rashid Hassan (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
This research is entitled: The Role of cooking Programs in Kurdish TV Channels on the development of cooking art on Women. The study was conducted by the researcher. This research consists of the research problem and its question, as well as the purpose and importance of the research. The researcher used the questionnaire form as a tool for collecting information from the respondents. The researcher took the employees of the University of Sulaymaniyah only women as the sample of the number of (115) people, but after the distribution of the form researcher used (108) form because of damage and write off some of them, and also field or practical side of the research consists of tables and the recurrence of the percentage and commented by the researcher and The results of the research were written and the suggestions and recommendations were written. The research shows that the percentage of women who follow the cooking programs is 83.78. The reasons for preparing the cooking are preparing the food by 21.1%. Also, 55.9, and in general these programs learn to prepare food is new by 57.0, and therefore the result emerged Analysis of the causes of the role of the question of encouraging the programs to prepare the table attractively appeared 0.74 This is a reference to the strength of the effects of the first components, and also the results showed the use of some foods to prepare food or The cooking will not be used N by 0.72,